Determinación del valor nutricional, perfil de ácidos grasos y contenido de minerales de la harina de larva de “Hermetia illucens” criadas con sustratos de residuos - Huayllahua Lomas, Alexander (2024)
There is a growing interest in finding new protein sources for food production. The larvae of the black soldier fly (Hermetia illucens) are especially notable for their high content of proteins, beneficial fats and essential amino acids, making them a viable alternative for the human diet. In this study, the nutritional properties of flour derived from black soldier fly larvae collected in the Peruvian Amazon and raised in three types of organic waste were evaluated. The results indicate that the flours analyzed have a notable content of proteins (38.90 - 44.68%) and fats (26.96 - 31.01%), as well as significant concentrations of minerals such as potassium (1531.23 - 1876 .79 mg/100g) and calcium (516.32 – 1787.39 mg/100g), and low levels of sodium (7.86 – 20.12 mg/100g). It is notable that larvae fed with orange bagasse showed the highest levels of iron (36.32 mg/100g) and manganese (21.76 mg/100g). The fatty acid profile revealed the predominant presence of palmitic acid (15.47 – 22.25%), oleic acid (16.58 – 22.64%), and linoleic acid (11.90 – 26.51%) in the three flour samples. These results underline that flours derived from black soldier fly larvae in the Peruvian Amazon constitute a nutritionally valuable source due to their richness in proteins, minerals and unsaturated fatty acids.